Evaluation of Healthcare Service Digitalization Using the HOT-Fit Method - Ekananda, Ferio Pristiawan (Borong Newinera Publisher, 2025)
Digital transformation in the healthcare sector has become a crucial element in enhancing the quality, efficiency, and transparency of public services. This study aims to evaluate the success of healthcare service digitalization at RSUD dr. Hasri Ainun Habibie Gorontalo using the HOT-Fit (Human, Organization, Technology, and Net Benefit) framework. The research employed a quantitative approach with survey instruments administered to 104 respondents, consisting of both medical and non-medical staff. The findings indicate that all HOT-Fit indicators fall within the